3a^2b-[2ab^2-2(-a^2b+4ab^2)]-5ab^2,其中a=-2,b=1/2快

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/14 02:21:33
3a^2b-[2ab^2-2(-a^2b+4ab^2)]-5ab^2,其中a=-2,b=1/2快
xMN0U8Nfb'AI7p DNmBSĞ {`E *<ߌ^-9Z9Ŏ&LwL*"oOHnY<}C}_[uiy[]ݮ;ꦫ]svP10ioV"V*AT L "11hf *(1R(DpY+Q^b//U '4FJ2,H/6.wYrا3邞>!bhc8@LM`j+>gm6>Wy

3a^2b-[2ab^2-2(-a^2b+4ab^2)]-5ab^2,其中a=-2,b=1/2快
3a^2b-[2ab^2-2(-a^2b+4ab^2)]-5ab^2,其中a=-2,b=1/2

3a^2b-[2ab^2-2(-a^2b+4ab^2)]-5ab^2,其中a=-2,b=1/2快

3a^2b-(-6ab^2+2a^2b)-5ab^2
=a^2b+6ab^2-5ab^2
=a^2b+ab^2
=ab(a+b)
=-2*1/2 *(-2+ 1/2)
=2- 1/2=3/2